Предмет: Математика,
автор: gulzhanat141010
4) (2x+3(x+y)-11=0, 7(x+3y) - 6x + 59 = 0. 195 19 ngr
Ответы
Автор ответа:
0
{2x+3(x+y)-11=0
{7(x+3y)-6x+59=0
{5х=-3у+11
{7(х+3у)-6х+59
{х= -3/5 у + 11/5
{7(х+3у)-6х+59
7(-3/5 у + 11/5 +3у) -6(-3/5у+11/5)+59=0
84/5 у + 77/5 + 18/5 у - 66/5 + 59=0
102у+306=0
102у=-306
у=-3
х=-3/5 * (-3) + 11/5
х=9/5+11/5
х=4
(х;у)=(4;-3)
{7(x+3y)-6x+59=0
{5х=-3у+11
{7(х+3у)-6х+59
{х= -3/5 у + 11/5
{7(х+3у)-6х+59
7(-3/5 у + 11/5 +3у) -6(-3/5у+11/5)+59=0
84/5 у + 77/5 + 18/5 у - 66/5 + 59=0
102у+306=0
102у=-306
у=-3
х=-3/5 * (-3) + 11/5
х=9/5+11/5
х=4
(х;у)=(4;-3)
Автор ответа:
0
Ответ: ( 4 ; - 3 )
Похожие вопросы
Предмет: Физика,
автор: papinadarina2009
Предмет: Алгебра,
автор: milana030211
Предмет: Английский язык,
автор: qwerty99911
Предмет: Геометрия,
автор: lili1717171717
Предмет: Химия,
автор: Аноним